Prove that ZPQM = ZPRM.
In the given figure, PQ = PR and MQ = MR.
P.
M
Q
R
Attachments:
![](https://hi-static.z-dn.net/files/d31/3bc3bfbaec94c1c9697d6f4212824139.jpg)
Answers
Answered by
6
Answer:
In ∆PQR, we have
PQ = PR
Angle PQR = Angle PRQ __________________ (¹)
(ISOSCELES TRIANGLE PROPERTY)
In ∆MQR, we have
MQ = MR
Angle MQR = Angle MRQ _________________(²)
(ISOSCELES TRIANGLE PROPERTY)
Now, subtracting both the equation
Angle PQR – Angle MQR = Angle PRQ – Angle MRQ
We have,
Angle PQM = Angle PRM
Similar questions